A design of an artificial marsh for treating waste water in the UNMSM - Llagas Chafloque, Wilmer (2006)
In this work an alternative is presented for the wastewater treatment in the University City of the UNMSM with the use of wetlands. Many «natural systems» they are being considered with the purpose of the wastewater treatment and control of the contamination of the water. The interest in the natural systems this based on the conservation of the resources associated with these systems like opposed to the process of conventional for wastewater treatment that is intensive regarding the energy use and chemical. The wetlands are one of the many types of natural systems that can be used for the treatment and control of the contamination. According to U.S. EPA (1983). «A wetland is built specifically with the purpose of to control the contamination and to manage the waste, in a place where a natural wetland exists. The form in that these wetlands works has similarity with the biological processes that are given in the nature and in the filters for leak used in the conventional treatment plants (Wolverton, 1988). The objectives of this work are: to design a system of wetlands type system of free superficial water (SFSW) for the wastewater treatment in the University City of the UNMSM and to describe the mathematical formulation of the biological processes in the wetlands. The wetlands would be receiving the residual waters coming from the net of sewer system of the University City.